A Study of Linguistic Landscape in Culinary Business - Qulub, Muhammad Farihul; Rusmawati, Roosi (Balai Bahasa Kalimantan Tengah, 2024)
Linguistic landscape becomes a symbol of the presence of language in public spaces, depicting the representation of written language seen in public areas such as roads, tourist attractions, buildings, and food business complexes. The choice of language and function is necessary in response to the linguistic landscape of an area with a strong culinary business reputation for young people. This article aims to explain the choice and function of language as the primary source of reasons for language use in the linguistic landscape of the food business (LL). Data collection techniques used are (1) Observation, (2) in-depth observations, and (3) drawing conclusions against the examination of previous articles published in publications related to investigations in this particular study. Data dominated by bottom-up signage, such as shop names, advertisements, and signs of street food stalls, were collected from signboards in areas where many young people gather to shop, stroll, look, and eat. The results of this study show that bilingual Indonesian-English dominate language contestation in the area. In addition, slang is also found in commercial areas. This research reveals a variety of languages in the culinary business that is dominated by young people. It reports that English is most widely used in signs compared to Indonesian, Javanese, or the mother tongue of the local people. AbstrakLanskap linguistik menjadi simbol kehadiran bahasa di ruang publik yang menggambarkan representasi bahasa tertulis yang terlihat di area umum, seperti jalan, tempat wisata, bangunan, dan kompleks bisnis makanan. Pilihan dan fungsi bahasa diperlukan sebagai tanggapan terhadap lanskap linguistik suatu daerah dengan reputasi bisnis kuliner yang kuat. Artikel ini bertujuan menjelaskan pilihan dan fungsi bahasa sebagai sumber utama penggunaan bahasa dalam lanskap linguistik bisnis makanan (LL). Teknik pengumpulan data yang digunakan ialah (1) observasi, (2) pengamatan mendalam, dan (3) penarikan kesimpulan terhadap pemeriksaan artikel sebelumnya yang diterbitkan dalam publikasi yang berkaitan dengan investigasi dalam studi khusus ini. Data yang didominasi oleh papan nama bottom-up, seperti nama toko, iklan, dan tanda warung makan jalanan, dikumpulkan dari papan nama di daerah-daerah tempat banyak anak muda berkumpul untuk berbelanja, berjalan-jalan, melihat-lihat, dan makan. Hasil penelitian ini menunjukkan bahwa bilingual bahasa Indonesia-Inggris mendominasi kontestasi bahasa di daerah tersebut. Selain itu, bahasa gaul juga ditemukan di area komersial. Penelitian ini mengungkapkan ragam bahasa dalam bisnis kuliner yang didominasi oleh anak muda. Bahasa Inggris paling banyak digunakan dibandingkan dengan bahasa Indonesia, Jawa, atau bahasa ibu masyarakat setempat.